ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP MELALUI PEMBELAJARAN INKUIRI - Warniasih, Kristina; Kurniawati, Ririn Meila; Utami, Niken Wahyu (Universitas Papua, 2019)
The research aims to know student’s mathematics critical thinking ability at the inquiry learning process of P flat side geometry of cube and cuboid class VIII B SMP Negeri 1 Sentolo. This kind of research is qualitative research. The research subject was six students of class VIII B SMP Negeri 1 Sentolo, that consist of two students of high class, two students of the middle class, and two students of low class. The collected data was in the form of written and oral. The written data was obtained from the test, and the oral data was obtained from the interview. Mathematic critical thinking ability was measured based on Ennis’ indicator. The research result showed that after student followed the learning process with guided inquiry learning method, high-class students can build the entire indicator of mathematic critical thinking ability correctly and completely, middle-class students can built the entire indicator of mathematic critical thinking ability correctly but there were little problems at the indicator 1, 2, 3 and 4, whereas low-class students can build the entire indicator of mathematic critical thinking ability correctly but there were little problems at the indicator 2 and 3. Besides, they less in indicator 1 and 4.